Pengembangan Lembar Kerja Siswa Terintegrasi Nilai-nilai Keislaman pada Materi Bilangan - Halistin, Halistin; Patih, Tandri; Firman, Alfira Yuliana; Karmini, Karmini (Jurnal Tadris Matematika, 2023)
Research on the development of Student Worksheets (LKPD) integrated with Islamic values is motivated by the absence of LKPD that integrates Islamic values in the mathematics learning process and the low interest in learning MTs Asy-Syafi'iyah Kendari students. This study aims to develop valid, practical, and effective LKPD. The research method used is research and development with the ADDIE model. The results showed that the LKPD integrated with Islamic values was very valid to be used in the learning process based on the results of the validity by material experts of 3.73 (very valid) and the results of the validity of religious experts at 3.07 (valid). LKPD is also very practical to use in the learning process at MTs Asy-syafi'iyah Kendari based on assessing teacher responses and student responses. The effectiveness of LKPD can be seen from the students' mathematics learning outcomes, where the results show that there are differences in the mathematics learning outcomes of class VII MTs Asy-Syafi'iyah Kendari before and after LKPD is used in the learning process, based on the results of the Wilcoxon test with a significance value of 0.018.